Improvement of the management system of a road transport enterprise - Guo, Jintong (Харківський національний автомобільно-дорожній університет, 2025)
In the qualification work, a study of the theoretical and methodological foundations for improving the management system of RTE under modern conditions of digitalization is carried out. The thesis develops a management system for a road transport enterprise based on structural-functional and cybernetic principles, with a clear differentiation between the managing and managed subsystems. An analysis of the organizational and technical level of the road transport enterprise is conducted, including an examination of its current operating conditions, organizational structure, management apparatus, and existing management systems. Particular attention is paid to the implementation of digital management tools, specifically a remote fleet management system and digital transport planning instruments. The implementation of the proposed solutions enables improved responsiveness of managerial decisionmaking, more efficient use of resources, enhanced planning accuracy, and better control over the execution of transport processes. Forecast assumptions regarding the development of the research object indicate that the implementation of the developed management system and modern digital technologies will contribute to increased operational efficiency of the road transport enterprise, strengthening its competitiveness, and ensuring sustainable development in a dynamic external environment.
Keywords: management system; personnel; management apparatus; analysis; remote fleet management system; management organization; evaluation; efficiency